The effect of psychological state and social support on nail-biting in adolescents: An exploratory study - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN (SAGE PUBLICATIONS LTD, 2017)
Nail-biting is one of the most common behavioral problems in children. This study aimed to examine factors affecting nail-biting among adolescents and the effects of psychological state and social support on nail-biting. This cross-sectional study was conducted between January and May of 2014 in seven schools in Istanbul (N=724). Data were collected using the Personal Information Form, Brief Symptom Inventory, and Child and Adolescent Social Support Scale. This study found that 48.2% of adolescents in the 11- to 17-years-old age group had a habit of nail-biting. Anxiety, depression, negative self image, somatization, hostility, and three global index scores of adolescents who bit their nails were significantly higher than in those who did not. Social support scores of those who bit their nails were significantly lower than in those who did not in the mother' and classmates' subscales and total scores. Psychological state and social support were factors affecting nail-biting among adolescents.
Keywords: adolescents; Brief Symptom Inventory (BSI); family support; nail-biting; psychological state; social support; FOCUSED REPETITIVE BEHAVIORS; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; SKIN PICKING; ONYCHOPHAGIA; PREVALENCE; CHILDREN; SAMPLE; IMPACT; HABIT